The effect of using educational modules according to the constructive method in improving some football skills of students (Journal of the College of Basic Education, 2024)
The study aims to identify the extent of the impact of using sequential (inter) tests according to the constructivist method in developing and developing some technical skills in football among students of the College of Physical Education and Sports Sciences. The study population was third-year students in the College of Physical Education and Sports Sciences at the University of Maysan, for the academic year. (2023-2024), and the researchers used the experimental method according to the use of one group of interconnected samples in addition to using means of collecting information and data, and educational units were prepared according to the constructivist method in football, interspersed with a group of football skill tests for a group of technical skills in football, while the study included the most important Conclusions including:- Using the method of sequential tests according to the constructive method in football will be more effective and interesting during the performance of the educational units. The most important recommendations were:- Emphasis on the continuous use of skill tests during the study period by professors and specialists.- Combining different teaching methods and football skill tests to serve the educational process.